Molecular Diagnosis of Cetacean Morbillivirus in Beaked Whales Stranded in the Canary Islands (1999–2017) - Idaira Felipe-Jiménez; Antonio Fernández; Manuel Arbelo; Simone Segura-Göthlin; Ana Colom-Rivero; Cristian M. Suárez-Santana; Jesús De La Fuente; Eva Sierra (Veterinary Sciences, 2022)
A retrospective survey for detecting the cetacean morbillivirus (CeMV) was carried out in beaked whales (BWs) stranded in the Canary Islands (1999–2017). CeMV is responsible for causing worldwide epizootic events with the highest mass die-offs in cetaceans, although the epidemic status of the Canarian Archipelago seems to be that of an endemic situation. A total of 319 tissue samples from 55 BWs (35 Cuvier’s BWs and 20 specimens belonging to the Mesoplodon genus) were subjected to the amplification of a fragment of the fusion protein (F) and/or phosphoprotein (P) genes of CeMV by means of one or more of three polymerase chain reactions (PCR). RNA integrity could not be demonstrated in samples from 11 animals. Positivity (dolphin morbillivirus strain (DMV)) was detected in the skin sample of only a subadult male Cuvier’s BW stranded in 2002, being the earliest confirmed occurrence of DMV in the Cuvier’s BW species. The obtained P gene sequence showed the closest relationship with other DMVs detected in a striped dolphin stranded in the Canary Islands in the same year. A phylogenetic analysis supports a previous hypothesis of a cross-species infection and the existence of the circulation of endemic DMV strains in the Atlantic Ocean similar to those later detected in the North-East Atlantic, the Mediterranean Sea and the South-West Pacific.